2015
DOI: 10.1007/s12576-015-0422-3
|View full text |Cite
|
Sign up to set email alerts
|

Partial cavopulmonary assist from the inferior vena cava to the pulmonary artery improves hemodynamics in failing Fontan circulation: a theoretical analysis

Abstract: Cavopulmonary assist (CPA) for failing Fontan patients remains a challenging issue in the clinical setting. To evaluate the effectiveness of a partial CPA from the inferior vena cava (IVC) to the pulmonary artery (PA), we performed a theoretical analysis using a computational model of the Fontan circulation. Cardiac chambers and vascular systems were described as the time-varying elastance model and the modified three-element Windkessel model, respectively. A rotational pump described as a non-linear function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Shimazu et al [15] reported that IVC assist is more suitable This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimazu et al [15] reported that IVC assist is more suitable This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication.…”
Section: Discussionmentioning
confidence: 99%
“…Shimazu et al [15] reported that IVC assist is more suitable for Fontan cavopulmonary support. They modelled a similar size example patient with weight=75 kg and BSA=1.9 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, these models have been applied to describe the active and passive elastance of LV (Zhong et al, 2005), contractile function of isolated LA (Hoit et al, 1994; Pironet et al, 2013), as well as ventricular–arterial interaction in the systemic and pulmonary circulations (Segers et al, 2003). The time‐varying elastance model has also been used to understand the effects cardiovascular diseases on exercise capacity (Fan et al, 2022), left and right heart function (Keshavarz‐Motamed et al, 2011; Koeken et al, 2012; Kung et al, 2014; Sano et al, 2003; Shimizu, Kawada, Une, Shishido, et al, 2016; Young et al, 2013) as well as simulate heart failure treatments such as the Fontan operation (Walker & Stuth, 2004) and ventricular assist device (Shimizu, Kawade, Une, Fukumitsu, et al, 2016). The time‐varying elastance model has also been modified based on the rule‐of‐mixture to take into account heterogeneous behavior in the LV due to mechanical dyssynchrony (Fan et al, 2020; Fan, Namani, Choy, Awakeem, et al, 2021), regional ischemia (Sunagawa et al, 1983) and myocardial infarction (Witzenburg & Holmes, 2019).…”
Section: Cardiac Mechanicsmentioning
confidence: 99%
“…Percutaneous axial-flow systems enhancing inferior vena cava blood flow towards the pulmonary arteries have been designated for partial cavopulmonary support in mediumterm support settings. [12][13][14][15] Similarly, an intravascular axial assist device for combined superior and inferior vena cava support has been proposed. 16 Novel concepts involve aortic pressuredriven pumps for cavopulmonary support from the inferior vena cava to the pulmonary arteries.…”
Section: Fontan Palliation By Total Cavopulmonary Connection (Tcpc)mentioning
confidence: 99%